Accusations of ethical violations at the Regional Social Work Council in Paraná - Mirales, Rosana (Argumentum, 2021)
This text presents the dynamics adopted in determining the relevance of the accusations of ethical violations received by the Regional Social Work Council in Paraná State (CRESS-PR, in Portuguese) and the findings of the complaints processes that were heard between 1993 and 2007, as recorded in the completed and archived files. The research was guided by bibliographic references on the social ethics of the social worker and is adopted as a method that favors the required systematization of the readings of the processes. During this period, there were 40 ethical processes: 17 in Curitiba and 23 in 16 other municipalities in the state of Paraná; 26 were upheld and received penalties of private warning (17), temporary suspension from 90 days up to 2 years (6), public warning (2), and dismissal (1). 12 appealed to the appellate court, of which 2 were annulled and reinstated, in 5 the results of the trial were upheld, and in 5 the penalties were revised down.